All inclusive? - Studien zu Inklusion und Hörschädigung in Bildung und Freizeit. - (:unkn) unknown (Kovac, 2016)
Die Beiträge setzen sich mit dem Phänomen der Inklusion auseinander und beleuchten unterschiedliche Aspekte oder Fragestellungen, die aufzeigen, wie mannigfaltig die Facetten der Inklusion sind. Die Artikel basieren mehrheitlich auf Abschlussarbeiten (Bachelor-, Master- oder Zulassungsarbeiten) der jeweiligen Autoren, die allesamt im Themenfeld von Inklusion und Hörschädigung entstanden sind, ohne die Beschränkung auf rein schulische Aspekte. Zwar können aus den kleinen Stichproben nicht pars pro toto allgemeingültige Richtlinien abgeleitet, aber dennoch Tendenzen aufzeigt werden, wie der Vision der Inklusion Stück für Stück näher zu kommen ist. Jede der Forschungseinheiten birgt neue Erkenntnisse, die nicht in uniinternen Archiven verstauben und in Vergessenheit geraten sollten.

Productivity differentials of workers between urban and rural regions are usually explained by increasing returns to scale due to agglomeration. These increasing returns to scale are called agglomerations economies. We contribute to the literature as we analyse regional differences in agglomeration and individual location decisions of workers jointly. We use a panel dataset for 412 German Nuts3-regions for the years from 1996 to 2008. Beside detailed formal educational data our dataset comprises information about 33 different fields of profession. The information about the professions serves as detailed proxies for the skills possessed by the workers. In the first empirical chapter we analyse the vertical sorting model. Checking for endogeneity, year- and region specific effects we can confirm the conclusions from our theoretical analysis: Employees profit heterogeneously form density. Agglomeration may thus be a driving force of workers sorting. In the second empirical chapter we investigate horizontal sorting. We first identify regional specialisations in the occupational structure and group regions with similar structures together. Second, we analyse the impacts of agglomeration in the different clusters on labour productivity. The empirical results commit the theoretical implications: We find evidence for horizontal sorting such that workers with skills in different fields locate in different regions. We further find that workers in these specialised regions profit differently from agglomeration. Lastly, we examine inter-regional integration and its dependence on the occupational profiles of the regions.
Keywords: Bildungswesen; Schule; Freizeit; Behinderter; Integration; Hörgeschädigter; Inklusion